2010
DOI: 10.1002/smll.201001168
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Field Emission of Nitrogen‐Doped Carbon Nanotubes/Reduced Graphene Hybrid Films

Abstract: The outstanding flexible field emission properties of carbon hybrid films made of vertically aligned N-doped carbon nanotubes grown on mechanically compliant reduced graphene films are demonstrated. The bottom-reduced graphene film substrate enables the conformal coating of the hybrid film on flexible device geometry and ensures robust mechanical and electrical contact even in a highly deformed state. The field emission properties are precisely examined in terms of the control of the bending radius, the N-dopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
60
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 116 publications
(61 citation statements)
references
References 29 publications
0
60
1
Order By: Relevance
“…The low turn on fi eld of 1.86 V/mm and fairly high β value of 3000 are attriuted to the direct and robust electrical contact between CNTs and the bottom Au substrate. [ 35 ] In summary, we have demonstrated a facile and universal method for surface nanopatterning, which is particularly useful for low surface energy substrates, such as Tefl on, graphene, and gold. Those materials have been longstanding challenges for surface nanopatterning thus far.…”
mentioning
confidence: 99%
“…The low turn on fi eld of 1.86 V/mm and fairly high β value of 3000 are attriuted to the direct and robust electrical contact between CNTs and the bottom Au substrate. [ 35 ] In summary, we have demonstrated a facile and universal method for surface nanopatterning, which is particularly useful for low surface energy substrates, such as Tefl on, graphene, and gold. Those materials have been longstanding challenges for surface nanopatterning thus far.…”
mentioning
confidence: 99%
“…For example, Chen at al reported the FE properties of NH 3 plasma processed CNTs, and they found that the treated CNTs have a much lower E on than that of the untreated ones [16]. Similar strategies have also been used to improve the FE properties of CNTs, such as oxygen [17,18] and nitrogen processing [19,20]. However, there are still great efforts need to be made to further lower the E on and E th , ameliorate the FE stability, and deeply understand the FE enhancement mechanism.…”
Section: Introductionmentioning
confidence: 95%
“…As a result, nitrogen-doped CNTs or CNFs recently have attracted greater attention. Owing to the highly ordered structure of CNTs and CNFs, the most common method for nitrogen inclusion is the use of in situ nitrogen-doping approach (Lee et al, 2011;O'Byrne et al, 2011;Lepró et al, 2012).…”
Section: One-dimensional Nitrogen-doped Carbon Nanotubes and Nanofibersmentioning
confidence: 99%